2020
DOI: 10.1016/j.stemcr.2020.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Reprograms Alveolar Progenitor Cell Metabolism in Response to Lung Injury

Abstract: Autophagy is a protective cellular mechanism in response to stress conditions. However, whether autophagy is required for maintenance of the alveolar epithelium is unknown. Here, we report that the loss of autophagy-related 5 (Atg5) in AT2 cells worsened bleomycininduced lung injury. Mechanistically, during bleomycin injury, autophagy downregulated lipid metabolism but upregulated glucose metabolism in AT2 cells for alveolar repair. Chemical blockade of fatty acid synthesis promoted organoid growth of AT2 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 32 publications
0
38
0
Order By: Relevance
“…Previously, Li et al showed that after lung injury with bleomycin (under SD conditions), glycolytic and pentose phosphate pathways are promoted, whereas fatty acid synthesis is repressed in mouse AT2 cells, which eventually results in fibrosis resolution and epithelial repair [31]. Therefore, we propose that in the presence of the HFD-induced excess in fatty acids, AT2 stem cells are pushed toward FAO as an energy source, rather than the classic glycolysis, thus impairing its repair capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Li et al showed that after lung injury with bleomycin (under SD conditions), glycolytic and pentose phosphate pathways are promoted, whereas fatty acid synthesis is repressed in mouse AT2 cells, which eventually results in fibrosis resolution and epithelial repair [31]. Therefore, we propose that in the presence of the HFD-induced excess in fatty acids, AT2 stem cells are pushed toward FAO as an energy source, rather than the classic glycolysis, thus impairing its repair capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, activation of MTORC1 in macrophages by selective deletion of Tsc2 leads to excessive granuloma formation, a clinical implication for sarcoidosis (Linke et al , 2017 ). In addition, defective autophagy in progenitor alveolar type 2 (AT2) cells aggravates bleomycin‐induced lung injury, as it reduces AT2 cell stemness by reprogramming their metabolism (Li et al , 2020a ). Consistently, bleomycin‐induced upregulation of ANXA2 (Annexin A2) perturbs the autophagic flux by limiting TFEB nuclear translocation (Wang et al , 2018a ).…”
Section: Pulmonary Disordersmentioning
confidence: 99%
“…The lungs are frequently exposed to microbes and pollutants, thus establishing environmental adaptation that sustains immune tolerance, alleviates tissue injury, and secures gas exchange [ 7 ]. Given the clonal analysis and organoid culture together with lineage tracing mouse models, an increasing body of evidence has shown that there exist heterogeneous and complex resident epithelial progenitor or stem cells in the lung [ 69 , 70 , 71 , 72 , 73 ]. They generally divide rarely and are quiescent but proliferate and differentiate rapidly to accelerate the restoration of the surrounding epithelium since the lung is injured [ 74 ].…”
Section: Macrophages and Lung Repairmentioning
confidence: 99%